Intracranial Metastasis as the Initial Presentation of a Young Woman with Luminal B Her-2 Positive Stage 4 Breast Cancer - Gultom, Santi Christiani; Oehadian, Amaylia (International Journal of Integrated Health Sciences, 2020)
Objective: Breast cancer is the second most common cause of brain metastasis (BM) among all of the solid cancers, with metastases occurring in 10%–16% of patients and in as many as 30% of autopsy studies. Breast cancer-related BM usually has a poor prognosis and survival rate in the absence of any treatment within 2 months. Survival after BM is related to the subtype of the primary tumor. Human epidermal growth factor-2 (HER-2)-positive patients have a significantly better prognosis compared with other subtypes. The prognosis for the majority of patients with BM remains poor, despite local and systemic therapies, with a median survival of around 10 months.Methods: This case is interesting because our patient is very young, diagnosed with BM before breast cancer was identified, bit still surviving 12 months after her BM diagnosis. A 19-year old woman presented with seizures, vomit and headaches.Results: A cranial CT-scan showed an intracranial mass. The intracranial tumor was removed, and yielded a histopathological result of metastatic adenocarcinoma. Further examination found a lump in her right breast. She was diagnosed with intracranial metastatic stage 4 luminal B Her 2(+) breast cancer. She was referred for WBRT, a mastectomy, chemotherapy with docetaxel cyclophosphamide 4 cycles, followed by 12 cycles of trastuzumab, and continued treatment with tamoxifen and goserelin. The last PET-Scan showed no residual disease.Conclusion: Breast cancer as the primary tumor should be considered in women with a metastatic brain tumor. With appropriate treatment, even stage IV luminal B breast cancer with BM can still have a long life with good quality.